The Application of Discovery Learning to Improve Students' Understanding of Asmaul Husna Material in Class VII of Kepenuhan Islamic Junior High School in the 2023/2024 Academic Year - Jazrizal, Jazrizal; Nismar, Nismar; Supriyadi, Supriyadi (Indonesian Journal of Basic Education, 2024)
This study aims to analyse the application of Discovery Learning method in improving students' understanding of Asmaul Husna material in class VII of Kepenuhan Islamic Junior High School. The research method used was classroom action research (PTK) which was carried out in two cycles. The subjects of this research were students of class VII of Kepenuhan Islamic Junior High School in the 2023/2024 academic year. The instruments used included observation sheets, comprehension tests, and student response questionnaires. The results showed that the application of Discovery Learning was able to improve students' understanding of Asmaul Husna material, which was indicated by an increase in the average score of the comprehension test from the first cycle to the second cycle. In addition, students showed a positive response to this method, which was shown by an increase in active involvement in learning. Thus, the Discovery Learning method can be recommended as an effective approach in learning Islamic Religious Education (PAI), especially in understanding Asmaul Husna.